2022
DOI: 10.1039/d2ce00340f
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy: a methodological approach to the study of an old phenomenon

Abstract: Epitaxial growth is a long-standing crystallization phenomenon of great technological interest. Here we present the use of a new methodology approach making full use of the concept of adhesion energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Consequently, a low interface energy of around 0.3 J/m 2 is computed, indicating a small energetic gain when CuO is deposited as a film on top of a Cu 2 O substrate. In classical nucleation theory the barrier to nucleation arises due to the higher energy associated with a surface compared to bulk material and the strain that occurs across an interface due to the structural differences between two materials that are interacting . Thus, the high epitaxy between CuO and Cu 2 O would result in a lower strain between the two materials, expressed as a larger adhesion energy and smaller interface energy, which is in very good agreement with experimental observations.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Consequently, a low interface energy of around 0.3 J/m 2 is computed, indicating a small energetic gain when CuO is deposited as a film on top of a Cu 2 O substrate. In classical nucleation theory the barrier to nucleation arises due to the higher energy associated with a surface compared to bulk material and the strain that occurs across an interface due to the structural differences between two materials that are interacting . Thus, the high epitaxy between CuO and Cu 2 O would result in a lower strain between the two materials, expressed as a larger adhesion energy and smaller interface energy, which is in very good agreement with experimental observations.…”
Section: Resultssupporting
confidence: 76%
“…In classical nucleation theory the barrier to nucleation arises due to the higher energy associated with a surface compared to bulk material and the strain that occurs across an interface due to the structural differences between two materials that are interacting. 105 Thus, the high epitaxy between CuO and Cu 2 O would result in a lower strain between the two materials, expressed as a larger adhesion energy and smaller interface energy, which is in very good agreement with experimental observations. Moreover, the calculated adhesion energy of a Cu 2 O film epitaxially grown on a CuO substrate is almost 0.3 J/m 2 lower when compared to the deposition of CuO on top of Cu 2 O, suggesting a more stable synthesis pathway of CuO when used as a film rather than a substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…linear and area misfit <14%) (Mutaftschiev, 2001), allowing us to consider rapidcreekite as a precursor in gypsum precipitation via an epitaxial mechanism, promoting the formation of the 101 contact twin law. Indeed, epitaxial growth is an acknowledged phenomenon responsible for triggering different growth morphologies (Kellermeier et al, 2012;Bruno et al, 2022a) and polymorphs even if metastable phases are involved (Bruno et al, 2022b). The host phase forms a nanometre-thick intermediate structure whose faces act as the epitaxy substrate of the stable crystal, as reported in previous research where epitaxial relationships between two phases were investigated (Bruno et al, 2022a,b).…”
Section: The Role Of Comentioning
confidence: 76%
“…Some of these morphologies resemble some of the microfossils found in the Precambrian cherts. , Recently, our research team demonstrated that biomorphs could be considered to have been the first inorganic frameworks, in which the formed protobiomolecules became concentrated, conserved, aligned, and duplicated to give rise to the pioneer cell, and proposed that biomorphs are a reminiscence of the Precambrian cherts. The fact that they have not been dated as a fossil registry could have been because biomorphs were the ones to be actually formed, and their inclusion in sedimentary rocks is rather a biomineralization process through epitaxial growth. Epitaxy is a type of crystal growth between two different crystal phases. , However, it has not been documented whether biomorphs are a consequence of the dissolution of clays in alkaline environments (rich in alkaline earth metals) during the early stages of the Earth. The latter would foster the hypothesis that biomorphs or cherts existed since that era.…”
Section: Introductionmentioning
confidence: 99%
“…45−47 Epitaxy is a type of crystal growth between two different crystal phases. 48,49 However, it has not been documented whether biomorphs are a consequence of the dissolution of clays in alkaline environments (rich in alkaline earth metals) during the early stages of the Earth. The latter would foster the hypothesis that biomorphs or cherts existed since that era.…”
Section: Introductionmentioning
confidence: 99%